Epidemiological Characteristics of Occupational Accidents Reported to the National Center for Occupational Safety and Health for the years 2011-2013 - Abdulmahdi, Isra’a S.; Aljuboori, Suhair (Journal of the Faculty of Medicine Baghdad, 2015)
Background: Understanding the risk factors associated with injuries at workplace is an essential element to design and implement preventive measures for such injuries which are a significant source of disability, death and socioeconomic losses worldwide. Objectives: describe cases of occupational injuries with respect to person- place- time model. Materials and methods: Cross-sectional study done from October 2013 to October 2014 carried on 467 records of occupational injuries kept in the National Center for Occupational Safety and Health for the years 2011-2013. Results: Ahigher proportion of reported occupational accidents occurred in young male workers, during day time and among primary school graduates.The leading cause of fatality/permanent disability was electrical shock. Work-related road accidents had the highest fatality/permanent disability rate.Missing data in the field:age, duration of service, length of sick leave constituted 22.5%, 43% and 69.4% respectively. Conclusion: Work accidents could be prevented through the application and the use of safety techniques and equipments.Improving the quality and the completeness of data on occupational injuries is an important step to promote the performance of occupational health services.